Community consensus on core open science practices to monitor in biomedicine - Cobey, Kelly D.; Haustein, Stefanie; Brehaut, Jamie; Dirnagl, Ulrich; Franzen, Delwen L.; Hemkens, Lars G.; Presseau, Justin; Riedel, Nico; Strech, Daniel; Alperin, Juan Pablo; Costas, Rodrigo; Sena, Emily S.; et al. (PLoS biology, 2023)
The state of open science needs to be monitored to track changes over time and identify areas to create interventions to drive improvements. In order to monitor open science practices, they first need to be well defined and operationalized. To reach consensus on what open science practices to monitor at biomedical research institutions, we conducted a modified 3-round Delphi study. Participants were research administrators, researchers, specialists in dedicated open science roles, and librarians. In rounds 1 and 2, participants completed an online survey evaluating a set of potential open science practices, and for round 3, we hosted two half-day virtual meetings to discuss and vote on items that had not reached consensus. Ultimately, participants reached consensus on 19 open science practices. This core set of open science practices will form the foundation for institutional dashboards and may also be of value for the development of policy, education, and interventions.